Magnetorheological elastomers — An underestimated class of soft actuator materials. (August 2021) - Böse, Holger; Gerlach, Thomas; Ehrlich, Johannes
In this paper, the results of various investigations on the viscoelastic and magnetic properties of magnetorheological elastomers (MRE) in magnetic fields of variable strength, are reported. These characteristics have a strong influence on the behavior of MRE in various applications such as vibration damping and tunable vibration absorbers. Moreover, the actuation capabilities of MRE with different kinds of deformation in a magnetic field are considered. The degree of deformation depends on the magnetic field strength and its gradient and can reach about 10%. When removing the magnetic field, the MRE body relaxes back to its initial shape. MRE materials can be used for linear actuators, where the MRE body is deformed due to the attraction by a magnetic circuit acting from one side. Such linear actuators may be applied for haptic feedback and pumps. However, ring-shaped MRE bodies can also deform radially around their cylindrical axis, if the magnetic field is oriented correspondingly. This unusual type of deformation allows the realization of a proportional valve, whose opening is controlled by the magnetic field strength. Similar configurations can be used for controllable seals, for locking devices and even for inchworm drives. Various versions of this actuation principle are discussed in the paper.